Peningkatan Kemampuan Menulis Puisi dengan Metode Paralel Writing melalui Teknik Pengimajinasian Benda Abstrak Siswa Kelas X IPS 3 SMA Negeri 4 Pekanbaru - Lestari, Titik (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2019)
Learning Indonesian is not only learning languages ​​but also studying literature. Literary learning is also very important with the aim of giving a sense of love to literature and making students have the ability to appreciate and be able to judge the results of literary works. One aspect taught in learning literature is writing poetry. The motive of the importance of the learning process of writing poetry literary works for students is to improve reading and writing skills which can be used as a routine activity to improve achievement. Based on the results of observations on the learning patterns of Literature of Class students at X IPS 3 Pekanbaru of SMAN 4 Pekanbaru, students' poetry writing skills were still low. Students had difficulty in determining ideas, diction, and the first word in writing poetry. The achievement of the indicator editing poetry in accordance with the elements of poetry was not maximal, students were confused in determining diction and language style. It took a solution to these problems through innovation in the application of learning models. Pararrel writing based learning based on the imagination of abstract objects was one solution that can improve the power of writing poetry. So, this study aimed to improve students' poetry writing skills. The method used in this study was class action research with two cycles approach. Based on the results of the research that has been carried out, using the pararrel writing based learning model using imagination of abstract objects can improve poetry writing skills students at X IPS 3 Pekanbaru of SMAN 4 Pekanbarusignificantly.